Teaching aids innovation: spur gear system model kit - Muhd Hasanul Isyraf Mat Junoh; Normi Mohamad; Mohd Hanapi Jusoh (Southeast Asian Journal of Technology and Science, 2020)
This research describes the innovation produced to help the effectiveness of teaching and learning related to the topic gear found in DJJ5133 Engineering Design course. Previously students only saw pictures and video of the gear system. Instructors unable to bring real gear to class because it is heavy and dirty. Despite, this innovation of teaching aids is developed to help students to clearly understand the spur gear system and also power train system. The spur gear in this innovation is designed using CATIA V5 R20 software and been produced using a 3D printer. As a portable teaching and learning aid, Polylactic Acid (PLA) plastic is chosen as the main materials and the frame uses an aluminum profile. Apart from being used as a teaching aids, it is also suitable to be used as a gear ratio laboratory apparatus. Questionnaires were conducted on students and it was found that after using this teaching aids, mostly 100% student support this innovation produced and agree with the statement these teaching aids can help student understand more clearly about the basics of gear system.